The Influence of Product Quality and Prices on Customer Loyalty in The Tough Factory in Dusun I Panca Bakti, South Marbau Village, Marbau District, Labuhanbatu Utara District - Hasibuan, Midrawati; Sukmal, Jeni; Ritonga, Nurhabibah; Budiman, Syahrul; Munthe, Syafaruddin (Smart International Management Journal, 2024)
A This research aims to find out whether product quality has an influence on factory customer loyalty, product price on customer loyalty and to find out whether product quality and price have an influence on customer loyalty. The research was conducted in hamlet 1 Panca Bakti, South Marbau Village, Marbau District, North Labuhanbatu Regency, North Sumatra Province. The data collection method was carried out through surveys and questionnaires with the population in this study being all consumers of tofu factories in hamlet 1 Panca Bakti. The method for determining the sampling technique used is nonprobability sampling with an accidental sampling technique for a sample size of 41 people. The analysis used is multiple linear regression. The research results showed that product quality had a significant and positive effect on the level of customer loyalty with a t-count value of 4.797 > t-table value of 2.01 with sig. 0.004 <0.05 at the 95% confidence level. Product price influences the level of customer loyalty, where the t-count is 3.600 > t-table value 2.01 and the significance is smaller than 0.05 (0.017 < 0.05) at the 95% confidence level. Product quality and price simultaneously influence tofu customer loyalty in the research area where the F-count value is 4.125> F-table 3.21 and the significance value is 0.023 (<0.05) at the 95% confidence level.